The Effects of Progressive Muscle Relaxation in Reducing Neuropathic Pain in Type 2 Diabetes Patients - Fakhrudin Nasrul Sani; Musta’in; Sutiyo Dani Saputro (PT Inovasi Pratama Internasional, 2023)
Neuropathic pain in DM sufferers can be reduced by providing non-pharmacological therapy by providing relaxation or by providing education such as providing music therapy, relaxation and guided imagery. Physical exercise with relaxation that can be applied to DM patients includes Progressive Muscle Relaxation. The movements in PMR exercises aim to tighten and relax the muscles in one part of the body at a time to provide a feeling of physical relaxation. Relaxation can calm the nervous system so that the sufferer's body relaxes. This study aims to determine the effect of PMR in reducing neuropathic pain in patients with type 2 diabetes mellitus. The research design used the Quasy Experiment One Group Pretest – Posttest Control Group Design. The population in this study were all type 2 DM patients who experienced neuropathic pain. The sampling technique used was purposive sampling. Progressive Muscle Relaxation was given once a day for 7 days, and the pain scale was measured using the Visual Analog Scale (VAS) before and after administering PMR. The results of the study showed that the average pain level in the pre-test control group was 6 and post-test 5, while in the intervention group the average pre-test was 6 and post-test 4.81. The results of the Wilcoxon test in the control group showed a p value of 0.187 so there was no change in pain levels in the control group, while the intervention group showed a p value of 0.0001. The conclusion of this study is that there is a change in pain levels before and after PMR, so PMR can reduce neuropathic pain in patients with type 2 diabetes mellitus.